Pengaruh Pengeluaran Pemerintah dan Investasi Terhadap Kesempatan Kerja Melalui Pendidikan - Manuaba, Ida Bagus Adi Sutrisna; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 9, September 2016 (pp. 902 - 1010), 2016)
The research objective effect of government spending and investment on employment through education in the District / City of Bali Province 2008-2013. The study was conducted in the province of Bali.. Data collection techniques by directly recording data on the data in the form of government expenditures, the average data length of the school, the data development capital investment and data on the number of employment opportunities in the province of Bali with the technique of path analysis (path analysis). Based on the results of the analysis concludes government spending has a significant positive effect on the educational variables with significant value 0.000 <0.05, investments not directly affect education in the District / City in the province of Bali shown with significance 0.105> 0.05. Government spending and investment has a significant positive effect on the variable of employment opportunities with significant value 0.000 <0.05 and a significance of 0.000 <0.05. Education has a significant positive effect on the variable employment with a significance of 0.000 <0.05. Government spending and investment has a significant positive effect on the variable employment opportunities through education in the District / City of Bali Province 2008-2013 with a value of P1 = 0.561
Keywords: government spending, investment, education and employment